Obstacles and difficulties in accessing financing for MSMEs - Flores Castillo, Lilia Alejandra (2024)
This research work contextualizes the importance of internal credit in the private sector and its influence on the GDP per capita of the federal entities of México. By following a qualitative approach, a questionnaire is designed and applied to the main financial institutions of the Heroic City of Huajuapan de León to identify the causes of why financing has been denied to MSMEs in the region, the information obtained is tabulated, presented in percentage terms and graphs. In conclusion, it is identified that requirements such as collateral, financial information and guarantees continue to be the most common impediments to accessing bank credit. Likewise, the recommendation is that the businessman as an economic agent must be aware of the behavior of macroeconomic variables such as the interest rate, which definitely influence business decision-making, to carry out adequate planning of his economic commitments, new projects and to take advantage of opportunities that arise. URL: https://revistas.uta.edu.ec/erevista/index.php/bcoyu/article/view/2446